Design of fully and unrestraint continuous beams using BS5950:2000 and Eurocode 3 - Zhang, Kailong (2011)
As Singapore has already began implementing the use of Eurocodes in the construction industry in the first quarter of year 2010, many large organizations have since then followed suit so as to enable more economical, material-saving and cost-efficient buildings to be built. By switching to the Eurocodes, localized organizations are now qualified to bid for projects that are based in countries that, too, have adopted the Eurocodes since common grounds in civil and structural engineering are met.At this current point of time, designers who are used to the design procedures and the comprehensiveness in the British Standards would face much difficulty when carrying out the regular designing works due to the unfamiliarity of the Eurocodes.